Regulasi Hukum dalam Transaksi E-Commerce: Menuju Optimalisasi Pemanfaatan Teknologi Informasi - Budi Agus Riswandi (Jurnal Hukum IUS QUIA IUSTUM, 2002)
The development of informational technology have appeared new transaction pattern that is called electronic commerce (e-commerce). E-commerce is a transaction pattern which uses technology of information. Through e-commerce transaction, it gained much of things economically. But if it is viewed from jurisdical side, the e-commerce transaction model still have problem in law. Regulation of law support for optimalisation of utility thetechonology of information, especially in the e-commerce therefore must be realized. Concretization of this law regulation is realized in the form of the management on relations involved in transaction and it is not managementon its technology.